CHARACTERISTICS OF PATIENTS WITH CHRONIC KIDNEY DISEASE OF UNKNOWN ETIOLOGY (The Research of Medical Science Review, 2025)
OBJECTIVETo determine the clinical characteristics of patients with chronic kidney disease of unknown etiology.METHODOLOGYThis was a descriptive cross-sectional study done at the Hemodialysis Outpatient Department of Indus hospital in Karachi on the unknown etiology of adult CKD patients. The inclusion criteria were chronic kidney disease (CKD) stages I to V and age of the patient being 18 to 70 years, excluding patients with known identifiable causes or acute situations. The data were collected through demographic questionnaires, blood tests, and urine samples (24 hour). The analysis of data was done using SPSS 26, and descriptive statistics were produced to summarise the demographic and clinical variables. RESULTSIn a sample comprising 267 patients with average age was recorded as 51.6 ± 12.4 years, with a representation of 54.3% being female. A predominant proportion of the cohort was categorized within CKD stage IIIB (38.2%). The average serum creatinine levels were measured at 2.93 ± 1.29 mg/dL, with an estimated Glomerular Filtration Rate (eGFR) of 40.76 ± 13.84 mL/min/1.73 m², proteinuria levels at 356.12 ± 222.14 mg/day, and hemoglobin concentrations at 10.07 ± 1.75 g/dL. No statistically significant differences pertaining to gender or age were identified in the clinical parameters (p > 0.05).CONCLUSIONThese findings concluded that the patient with chronic kidney disease of unknown cause, recording high serum creatinine, low eGFR, low level proteinuria, anemia and trends to increase electrolyte imbalances. Such clinical features combining in the absence of classical risk factors underline the unique picture of CKDu and the necessity of regular biochemical tests to facilitate early diagnosis and risk stratification within populations exposed to them